Pengaruh Metacognition, Motivation, Dan Behavior Terhadap Hasil Belajar Metode Perkuliahan Daring Selama Pandemi Covid-19 (Studi Pada Mahasiswa Akuntansi Kota Bandar Lampung) - Shafa Alana Chrisman; Agus Zahron Idris (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The purpose of this research is to examine and analyze the effect of covid-19 pandemic on metacognition, motivation, and behavior in students performance. This research was conducted with accounting students from Bandar Lampung as subjects. The type of research in this study is quantitative data using tabulation results from questionnaires. The population in this study were accounting students at Lampung University, Bandar Lampung University, and Teknokrat University in Bandar Lampung. The data collection technique in this study used non-probability sampling with purposive sampling approach and obtained 225 respondents. Methods of data collection using questionnaires Analysis of the research data using SPSS as a calculation tool. The results of the study show that COVID-19 has an effect on the metacognition, motivation, and behavior of accounting students in Bandar Lampung.